Critical wetting in the two-dimensional Ising ferromagnet confined between inhomogeneous walls - Trobo, Marta Liliana (2014)
We present a numerical study of the critical wetting behavior of an Ising magnet confined between two walls, separated by a distance L, where short-range inhomogeneous surface magnetic fields act. So, samples are assumed to have a size L × M, L being the width and M the length, respectively. By considering surface fields varying spatially with a given wavelength or period (λ), H1(x, λ) with 1 ≤ x ≤ M, we found that the wetting temperature is given by the exact result of Abraham [D.B. Abraham, Phys. Rev. Lett. 44, 1165 (1980)] provided that an effective field given by the spacial average value (Heff ≡ 1 λ λ 0 H1(x, λ)dx > 0) is considered. The above results hold in the low wavelength regime, while for λ → ∞ and a bivaluated surface field (i.e., Hmax for x ≤ M/2, and δHmax for x > M/2, with 0 <δ< 1), one observes two almost independent wetting transitions, both being compatible with Abraham’s exact results corresponding to Hmax and δHmax, respectively. On the other hand, for H1(x, λ) = 0 but Heff = 0 bulk standard critical behavior results is observed.